Perforated necrotic appendix in Amyand's hernia treated with appendicectomy and simple suture repair of the inguinal hernia. Issue 11 (5th November 2019) - Malik, Muhamamd Isfandyar Khan; Abbas, Joshua; Shuttleworth, Paul; Qureshi, Nafees
Abstract : A 50-year-old man was referred to the emergency department by his general practitioner with a tender right-sided irreducible inguinal hernia (previously reducible), right-sided testicular pain and scrotal swelling. Clinical examination revealed a non-reducible, tender right inguinal-scrotal hernia and swollen right scrotum. Blood tests showed raised inflammatory markers. The patient went on to have a CT scan which was reported to show an indirect right inguinal-scrotal hernia possibly containing terminal ileum and small bowel mesentery. The scan also showed increased infiltrate changes within the hernia sac suggesting incarceration with possible early strangulation but no obvious evidence of bowel obstruction. The patient was taken to the operating theatre and found to have a large right inguinal-scrotal hernia containing pus and a perforated necrotic appendix. He went to have an appendicectomy and sutured repair of the hernia. Postoperatively, the patient made a good recovery and was discharged 2 days postsurgery.